Fact-checking and Transnational Cooperation: Analysis of the European Response to War Disinformation in the Context of the 2024 European Elections - Morejón Llamas, Noemí (2025)
Purpose. In response to the rise in disinformation linked to ongoing armed conflicts and its potential impact on the 2024 European Parliament elections, the European Fact-Checking Standards Network (EFCSN) launched the Elections24Check initiative, aimed at uniting verification efforts across the continent. This study seeks to examine the contribution of EU countries and fact-checking organizations to the project, as well as to analyze the characteristics of war-related information disorders. Methodology. To achieve this, a content analysis was conducted on 714 fact-checks published by Elections24Check during 2024, all related to the Russia–Ukraine and Israel–Palestine wars. Results and conclusions. The results highlight the prominent role of Spanish agencies and a stronger interest from European fact-checking journalism in the border conflict affecting Ukraine. While the initiative can be considered valuable within the realm of collaborative fact-checking, it still lacks internal coordination and a diversification of strategies beyond simple debunking. Original contribution. This research stands as the first comparative study to explore the relationship between war-related disinformation—particularly that stemming from the two conflicts generating the greatest concern among EU institutions—and the 2024 electoral period. It thus contributes to academic debate by emphasizing the need to strengthen coordination among European fact-checkers, while shedding light on their main practices and emerging trends.